Influence of Center Component Floating on the Load-sharing Characteristic of Planetary Transmission System - Yangyang Du; Xiaosun Wang; Xue Yang; Bo Jiao; Shijing Wu (Jixie chuandong)
In order to investigate the load-sharing performance of the 2K-H planetary gear transmission system， a translation-torsion coupling dynamics model is established with considering the nonlinear factors of time-varying meshing stiffness and the overall meshing error and so on， the dimensionless differential equations with 18 degrees of freedom of the system are deduced in this model. By solving the differential equations， the influences of the support stiffness of the center component and the clearance floating on the load-sharing performance of the planetary gear train are analyzed. It is shown that the floating amount of the component increases with the reduction of the support stiffness of the center component and the increase of the clearance of the shaft hole within a certain range， the load-sharing factor of the system decreases when the floating amount of the component increases.